2016
DOI: 10.14737/journal.jimb/2016/4.1.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aflatoxigenic Aspergillus in Food and Feed Samples from Karachi, Pakistan

Abstract: of food products spoilage and grains deterioration during storage, rendering them unfit for human consumption. Some of these contaminants, for instance, few species of Aspergillus and Fusarium produce mycotoxins in many food products. The quality of food and related products, such as seeds/grains, vegetables, fruits and processed products, are significantly deteriorated by these toxigenic strains (Lee et al., 2007). Different types of fungal toxins have been discovered so far, presenting different structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
3
6
0
Order By: Relevance
“…This can be attributed to the ability of Aspergillus flavus to grow on a variety of substrates across different environmental conditions, as well as its capability to produce numerous spores that remain viable, even under extreme conditions. These findings are in agreement with reports by several other studies who revealed a high prevalence of Aspergillus species in the contamination of rice grains from local markets [19,20,21]. In our case, this contamination might be due to the exposure of rice grains to fungal colonization during processing, transportation, and storage.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This can be attributed to the ability of Aspergillus flavus to grow on a variety of substrates across different environmental conditions, as well as its capability to produce numerous spores that remain viable, even under extreme conditions. These findings are in agreement with reports by several other studies who revealed a high prevalence of Aspergillus species in the contamination of rice grains from local markets [19,20,21]. In our case, this contamination might be due to the exposure of rice grains to fungal colonization during processing, transportation, and storage.…”
Section: Resultssupporting
confidence: 94%
“…Keeping in view the above results, it is obvious that the contamination level of mycotoxigenic fungi in rice grains sold at the markets is very high. Our results are in accordance with other reports demonstrating the importance of PCR assay techniques for detecting the aflatoxigenic potential of Aspergillus strains [20,21,31,32,33,34].…”
Section: Resultssupporting
confidence: 93%
“…As an additional example, Kaya-Celiker, in an interesting paper, successfully used Fourier transform mid-infrared and photoacoustic spectroscopy to identify and separate infected peanuts based on spectral characteristics [122]. Ibrahim and coworkers recently screened 102 feed samples (including poultry feed, cotton seed meal, and corn) for the presence of aflatoxin biosynthetic pathway genes ver-1, apa-2, and omt-1 using PCR assay, and thin-layer chromatography was performed to confirm the synthesis of aflatoxin in PCR-positive strains [123]. Nine samples exhibited the simultaneous presence of the three genes and all were capable of producing AFB 1 and AFB 2 .…”
Section: Bearing Of Aflatoxigenic Molds Isolation From Feedmentioning
confidence: 99%
“…Several food and feed samples were screened, as reported earlier, for the presence of aflatoxigenic Aspergillus strains (Ibrahim et al, 2016). Aspergillus parasiticus (FH44) was selected for the experiment on the basis of its toxicity.…”
Section: Fungal Strainmentioning
confidence: 99%
“…Aspergillus parasiticus (FH44) was selected for the experiment on the basis of its toxicity. This strain has shown the highest amount of AFs when isolated from a sample of maize (Ibrahim et al, 2016). Inoculum was prepared according to the method described by Ghadeer and Al-Delamiy (2012).…”
Section: Fungal Strainmentioning
confidence: 99%